Introduction au dossier spécial : Collaborations franco-japonaises en primatologie - James R Anderson; Tetsuro Mastuzawa (Revue de Primatologie)
The four papers in this special feature complement five others recently published in the journal Primates (including a slightly modified version of this editorial introduction, Anderson and Matsuzawa, 2016) further illustrating the breadth and depth of collaboration between Francophone and Japanese researchers in primatology. We hope that these collections of papers will provide the opportunity for scientists to look back at these collaborations, and to look forward to new ones.